INFECTIOUS DISEASES IN THE TIMURID ERA AND THEIR IMPACT ON SOCIO-CULTURAL LIFE (Scientific journal of the Fergana State University, 2025)
This article studies and analyses infectious diseases in the times of Amir Temur and Timurids, as well as their types and causes, on the basis of historical sources and scientific literature. Some remarks are made about the measures taken by medical institutions, doctors and the government against infectious diseases, as well as the impact of epidemics on socio-economic and scientific-literary processes in the country.